The Effect of the Self- Questioning Strategy in Teaching Social Studies Course on Developing learning process Among Middle School Students - Al-Shahrani, Sharaa Mohammad Omair; Najmuldeen, Hanan AbdulJalil (Journal of Educational and Psychological Sciences, 2022)
This research aims to identify the effect of the self-questioning strategy in teaching the social studies course to develop the learning process among first-grade intermediate students. For this purpose, the researcher used a quasi-experimental approach. A guide was prepared for the teacher to explain how to teach the Prophet’s era unit using a self-questioning strategy, and a scale of the learning process. The scale comprises (40) phrases. The research sample consisted of (51) female students in Jeddah city. The sample was divided into two groups: an experimental group consisted of (25) students who studied using the self-questioning strategy, a control group consisted of (26) students who studied in the usual way. Results showed significant differences at a level (α≤0.05) between mean scores of the experimental and control groups, in the post-measurement of the learning process scale as a whole in favor of the experimental group. The results indicate that there is an effect of using the questioning strategy. The researcher offered several recommendations, including the generalization of the guideline prepared by the researcher to implement the self-questioning strategy to develop the learning process. The second one is to train social studies teachers on the application of the self-questioning strategy and using scales that measure the learning process to develop it among students.
Keywords: Social studies; impact; self-questioning strategy; learning process